Enhanced antiferroelectric phase stability in La-doped AgNbO3: perspectives from the microstructure to energy storage properties. Issue 5 (14th January 2019) - Gao, Jing; Zhang, Yichi; Zhao, Lei; Lee, Kai-Yang; Liu, Qing; Studer, Andrew; Hinterstein, Manuel; Zhang, Shujun; Li, Jing-Feng
Abstract : High energy density was achieved in lead-free La-doped AgNbO3 antiferroelectric ceramics. Abstract : La-doped AgNbO3 lead-free ceramics were fabricated by conventional solid-state reaction, and the phase stability and energy storage properties were investigated. The temperature- and electric field-dependent dielectric constants show that the antiferroelectric (AFE) phase stability is enhanced via the La doping. Neutron diffraction was performed to obtain insights into the structural evolution with composition and temperature, where the local structural variation is found to involve subtle ion displacement as well as oxygen octahedral tilting, leading to the disruption of the long-range interactions, which is responsible for the enhanced AFE phase stability. As expected, the enhanced AFE phase stability, together with the improved breakdown strength, gives rise to a high energy density of 4.4 J cm −3 and an improved efficiency of 70%, which are achieved in 2 mol% La-doped AgNbO3 ceramics. Our research opens a new way to tailor the macroscopic properties by tuning the microstructure of AgNbO3 -based materials.